2019
DOI: 10.1177/1747021819847131
|View full text |Cite
|
Sign up to set email alerts
|

Why the whole is more than the sum of its parts: Salience-driven overestimation in aggregated tactile sensations

Abstract: Experimental psychology often studies perception analytically, reducing its focus to minimal sensory units, such as thresholds or just noticeable differences in a single stimulus. Here, in contrast, we examine a synthetic aspect: how multiple inputs to a sensory system are aggregated into an overall percept. Participants in three experiments judged the total stimulus intensity for simultaneous electrical shocks to two digits. We tested whether the integration of component somatosensory stimuli into a total per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…The difference in performance was significant (paired-sample t-test: t 14 = 3.5, p = .004, d = .90). Previous studies have also found that somatosensory aggregation tends to produce better performance than discrimination (Cataldo et al, 2019), possibly reflecting that the aggregate can be derived even when discrepancy between stimuli is unclear. Performance between the tasks was not correlated across participants (r = .20, p = .47), showing no evidence for a common computational factor underlying individual differences in performance.…”
Section: Behavioural Performancementioning
confidence: 93%
See 1 more Smart Citation
“…The difference in performance was significant (paired-sample t-test: t 14 = 3.5, p = .004, d = .90). Previous studies have also found that somatosensory aggregation tends to produce better performance than discrimination (Cataldo et al, 2019), possibly reflecting that the aggregate can be derived even when discrepancy between stimuli is unclear. Performance between the tasks was not correlated across participants (r = .20, p = .47), showing no evidence for a common computational factor underlying individual differences in performance.…”
Section: Behavioural Performancementioning
confidence: 93%
“…The ability to extract overall or average motion information from multiple, simultaneous motion cues has been described in vision (Watamaniuk & McKee, 1998;Watamaniuk et al, 1989) under the idea of ensemble perception (for review see Alvarez, 2011;Whitney & Yamanashi Leib, 2018). In touch, a few studies have investigated aggregation of tactile features such as intensity or frequency (Cataldo et al, 2019;Kuroki et al, 2017;Walsh et al, 2016). However, when an object held between fingers begins to move, the overall motion direction of the object can be also clearly perceived (Martin, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The difference in performance was significant (paired-sample t-test: t 14 = 3.5, p = .004, d = .90). Previous studies have also found that somatosensory aggregation tends to produce better performance than discrimination (Cataldo et al, 2019), possibly reflecting that the aggregate can be derived even when discrepancy between stimuli is unclear. Performance between the tasks was not correlated across participants (r = .20, p = .47), showing no evidence for a common computational factor underlying individual differences in performance of both averaging and discrimination tasks.…”
Section: Behavioural Performancementioning
confidence: 93%
“…The ability to extract overall or average motion information from multiple, simultaneous motion cues has been described in vision (Watamaniuk et al, 1989;Watamaniuk and McKee, 1998) under the idea of ensemble perception (for review see Alvarez, 2011;Whitney and Yamanashi Leib, 2018). In touch, a few studies have investigated aggregation of tactile features such as intensity or frequency (Walsh et al, 2016;Kuroki et al, 2016;Cataldo et al, 2019). However, when an object held between fingers begins to move, the overall motion direction of the object can be also clearly perceived (Martin, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Walsh et al, 2016;Cataldo et al, 2019) have also revealed that stimuli delivered to multiple fingers of the same hand are often integrated with unequal sensory weights, but not when they are delivered to two fingers on opposite hands. Capacity limitation in general enforces us to allocate available resources to more relevant stimuli.…”
Section: Introductionmentioning
confidence: 98%